Digitalisasi Madrasah: Strategi Kepala Madrasah Dalam Mewujudkan Quality Of Academic Service Berbasis Digital - Mohammad Ja'far As-shodiq; Mukhamad Sukur; Haris Syamsuddin; Brett Aaron Huggins (JoIEM (Journal of Islamic Education Management), 2025)
This study aims to identify and analyze the strategies of the madrasah principal in realizing a digital-based quality of academic service, which includes digital-based learning services, administrative services, and library services. The research method used is qualitative research with interviews, observations, and documentation as data collection methods. Data were analyzed using data condensation, data presentation, and conclusion drawing. The results of this study indicate that the madrasah principal's strategy in implementing digital-based learning services is carried out by preparing digital devices, creating the integrated SMARD MAN 1 learning platform, and improving teachers' digital competencies in technology usage. Digital administrative services are realized through two services, namely personnel services and correspondence services. Digital-based library services are realized through the procurement of hardware and software, the digitization of book collections and learning materials, and the development of an integrated digital library portal with SMARD MAN 1.